Visual Formation in the Poetry of Karim Shaghidil (Journal of the College of Basic Education, 2026)
Visual composition is one of the most important modern approaches to reading Arabic poetry, as it opens new horizons for understanding the relationship between language and image, and between text and vision. Contemporary poetry has transcended the boundaries of traditional auditory reception, transforming the page into a visual space where signs interact, and lines, spaces, and visual rhythms juxtapose, thus imbuing the text with a semantic layer parallel to its linguistic meaning. Through this conscious use of visual elements, the poet Karim Shaghidil allows the reader a deeper engagement, based on both visual perception and imagination.